Moses Hazen and the Canadian refugees in the American Revolution - Everest, Allan S. (Allan Seymour) (New York State study., 1976)
Moses Hazen recruited Canadians from Quebec and Nova Scotia to join the Continental Army. After the war, many received land grants on the northern frontiers of New York.